TET1 deficiency attenuates the DNA damage response and promotes resistance to DNA damaging agents. Issue 10 (3rd October 2017) - Coulter, Jonathan B.; Lopez-Bertoni, Hernando; Kuhns, Katherine J.; Lee, Richard S.; Laterra, John; Bressler, Joseph P.
ABSTRACT: Recent studies have shown that loss of TET1 may play a significant role in the formation of tumors. Because genomic instability is a hallmark of cancer, we examined the potential involvement of 10-11 translocation 1 (TET1) in the DNA damage response (DDR). Here we demonstrate that, in response to clinically relevant doses of ionizing radiation (IR), human glial cells made TET1-deficient with lentiviral vectors displayed greater numbers of colony forming units and lower levels of apoptotic markers compared with glial cells transduced with control vectors; yet, they harbored greater DNA strand breaks. The G2 /M check point and expression of cyclin B1 were greatly diminished in TET1-deficient cells, and TET1-deficient cells displayed lower levels of γH2A.x following exposure to IR. Levels of DNA-PKcs, which are DNA-PK complex members, were lower in TET1-deficient cells compared with control cell lines. However, levels of ATM were similar in both cell lines. Cyclin B1, DNA-PKcs, and γH2A.x levels were each rescued by reintroduction of the TET1 catalytic domain. Finally, cytosine methylation within intron 1 of PRKDC, the gene encoding DNA-PKcs, was significantly higher upon depletion of TET1. Taken together, this study illustrates the involvement of TET1 in the different arms of the DDR and suggests its loss results in the continued survival of cells with genomic instability.